Analisis Kualitas Udara Ambien Sebelum dan Setelah Pelaksanaan Pembatasan Sosial Berskala Besar di Jagakarsa Jakarta Selatan - Andini Sri Mulyani Mulyani; Tatan Sukwika; Ninin Gusdini (ECOTAS, 2022)
The determination of Large-Scale Social Restrictions (PSBB) resulted in a decrease in community activities outside the room. On the other hand, it has an impact on reducing emission levels in the air which describes the condition of air quality in the Jagakarsa. This study was to measure ambient air quality conditions referring to the Air Pollution Standard Index (ISPU). The method of analysis is descriptive-quantitative. ISPU parameters measured were PM10, CO, SO2, NO2, and O3. All parameters were tested by paired t-test. The measurement results on the status of ambient air quality were in the